1982
DOI: 10.1104/pp.70.5.1260
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylglycerol Synthesis in Spinach Chloroplasts: Characterization of the Newly Synthesized Molecule

Abstract: Intact chloroplasts from spinach (Spuiacia oleracea L., hybrid 424) readily incorporate I'4Ciglycerol-3-phosphate and 114CIacetate into diacylglycerol, monoacylglycerol, diacylglycrol, free fatty acids (only when acetate is the precursor), phosphatidic acid, phosphatidylcholine, and most notably phosphatidylglycerol. The fraction of phosphatidylglycerol synthesized is greatly increased by the presence of manganese chloride in the reaction mixture. PG2 is an important lipid component ofchloroplasts. Depending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…This resembles fatty acid labeling of procaryotic MGD in spinach leaves, which contained 18:1, 18:2, and 18:3 at the sn-l position, whereas 16:0 at the sn-2 position was not desaturated ( 15). In previous studies with intact organelles, desaturation of newly formed acyl groups was not only observed in MGD but also in SQD (1,14), PG (1,21,26), and PC (13). With ruptured chloroplasts we also detected desaturation in lipids other than MGD.…”
Section: Resultsmentioning
confidence: 92%
“…This resembles fatty acid labeling of procaryotic MGD in spinach leaves, which contained 18:1, 18:2, and 18:3 at the sn-l position, whereas 16:0 at the sn-2 position was not desaturated ( 15). In previous studies with intact organelles, desaturation of newly formed acyl groups was not only observed in MGD but also in SQD (1,14), PG (1,21,26), and PC (13). With ruptured chloroplasts we also detected desaturation in lipids other than MGD.…”
Section: Resultsmentioning
confidence: 92%
“…These observations are strengthened by the fact that phosphatidic acid and diacylglycerol synthesized ['4C]acetate [8] or a mixture of different acyl-CoA and/or acyl-ACP species [3] have a specific fatty acid pattern (i.e., with Cl8 fatty acids and Cl6 fatty acids respectively, on the sn-I and sn-2 position of the glycerol backbone). This pattern is identical to that found in MGDG from 16: 3-containing plants and in sulfolipids and phosphatidylglycerol synthesized either in vivo [9-121 or in vitro [6,7,13,14]. Therefore, it is important to localize precisely the enzymes involved in diacylglycerol biosynthesis in order to understand their role in plastid glycerolipid metabolism.…”
Section: Introduction Within Isolated Envelope Membranes From Eithermentioning
confidence: 78%
“…The addition of MnCl2 was reported to stimulate PG synthesis in spinach chloroplasts (28). However, the addition of MnC12 ( 1-4 mM) to pea chloroplasts had no significant effect on the proportion of label incorporated into PG, although the proportion of label present in PA and LPA appeared to increase slightly (data not shown).…”
Section: Resultsmentioning
confidence: 75%
“…It has been clearly demonstrated recently that isolated intact spinach chloroplasts can synthesize PG de novo from either acetate or glycerol 3-P under conditions of fatty acid synthesis (25,28). We have now utilized pea chloroplasts to investigate the pathway and localization of PG synthesis.…”
mentioning
confidence: 99%